KAJIAN INTERSEPSI CAHAYA MATAHARI TERHADAP PERTUMBUHAN TANAMAN KACANG HIJAU (Phaseolus radiata L.) VARIETAS LOKAL SABU PADA JARAK TANAM DAN PUPUK CAIR YANG BERBEDA - Maria Klara Salli; Yosefina Lewar; Masria Masria (Politeknik Pertanian Negeri Kupang, 2021)
The purpose of this study was to examine the effect of the growth of green bean local varieties of Sabu at different spacing and liquid fertilizer and to determine the relationship between sunlight interception and plant growth.The experimental design used was a factorial randomized block design with two factors, namely spacing is Plant spacing 40 cm x 20 cm , 40 cm x 25 cm , 40 cm x 30 cm and Type of Liquid Organic Fertilizer namely: NPK plus fertilizer, Nasa POC,Green Tonic Liquid Fertilizer, and POC ABG. The results showed that the difference in spacing and the type of liquid fertilizer affected the number of productive branches and the percentage of sunlight interception at the age of 5 week after planting (WAP) but did not influence other growth components. Spacing affects plant height at the age of 3 and 4 WAP and the percentage of light interception. Key Words: interception, plant growth, spacing, and liquid fertilizer